The relationship between sleep quality, snoring symptoms, night shift and risk of stroke in Chinese over 40 years old - Zhang, Yajing; Zhang, Ting; Xia, Xiaoshuang; Hu, Yahui; Zhang, Chao; Liu, Ran; Yang, Yun; Li, Xin; Yue, Wei (Frontiers in Aging Neuroscience, 2023)
Objectives To analyze the relationship between sleep quality, snoring symptoms, night shift and risk of stroke in Chinese population over 40 years old. Methods Based on the national screening and intervention program for high-risk population of stroke in 2016, 15,016 people completed the study of “the association between sleep and stroke,” 58,696 people completed the snoring questionnaire, and 58,637 people completed the night shift questionnaire. Results The proportion of coronary heart disease, hypertension, hyperlipidemia, diabetes, snoring, atrial fibrillation, stroke and high-risk group of stroke risk rating were higher in the group with poor sleep quality (p < 0.05). The proportion of high blood pressure, hyperlipidemia, diabetes, atrial fibrillation, transient ischemic attack (TIA), or high-risk group of stroke risk rating was higher in snoring group (p < 0.05). The body mass index (BMI), waist circumference, neck circumference, fasting blood glucose, triglyceride (TG), total cholesterol (TC), low density lipoprotein (LDL) and homocysteine (Hcy) levels in snoring group were higher than the non-snoring group, and high density lipoprotein (HDL) levels were lower (p < 0.05). People with TIA, high risk for stroke, and high blood pressure were higher in night shift workers than non-night shift workers (p < 0.05). The levels of BMI, fasting blood glucose, 2 h postprandial blood glucose, glycated hemoglobin, TG, TC, LDL, HDL and Hcy in night shift group were lower than the non-night shift group (p < 0.05). Conclusion Sleep quality, snoring and night shift might be related to the risk factors of stroke.